Prediction of the lower serum anti-Müllerian hormone threshold for ovarian stimulation prior to in-vitro fertilization using the Elecsys® AMH assay: a prospective observational study - Grynnerup, A. G. (Reprod Biol Endocrinol, 2019)
BACKGROUND: In assisted reproductive technology, prediction of treatment failure remains a great challenge. The development of more sensitive assays for measuring anti-Müllerian hormone (AMH) has allowed for the possibility to investigate if a lower threshold of AMH can be established predicting very limited or no response to maximal ovarian stimulation. METHODS: A prospective observational multicenter study of 107 women, < 40 years of age with regular menstrual cycle and serum AMH levels ≤ 12 pmol/L, treated with 300 IU/day of HP-hMG in a GnRH-antagonist protocol. AMH was measured before treatment start using the Elecsys® AMH assay by Roche Diagnostics. The ability of AMH to predict follicular development and ovarian response was assessed by receiver operating characteristics (ROC). Furthermore, the relationship between AMH at start of stimulation and cycle outcome was investigated using multivariate logistic regression analysis. RESULTS: Five out of 107 cycles (4.7%) were cancelled due to lack of follicular development and 60/107 (56%) women did not reach the classical hCG criteria for ovulation induction (≥ 3 follicles of ≥17 mm). An AMH threshold of 4 pmol/L predicted failure to reach the classical hCG criteria with 89% specificity and 53% sensitivity and an area under the curve (AUC) of 0.76 (95% CI 0.66–0.85). AMH predicted cycle cancellation due to lack of follicular development, using a cut-off value of 1.5 pmol/L, with a specificity of 96% and sensitivity of 80% (AUC = 0.92, 95% CI 0.79–1.00). A single-unit increase in AMH was associated with a 29% decrease in odds of failure to reach the classical hCG criteria (OR 0.71 95% CI 0.59–0.85, p < 0.01). The lowest AMH value compatible with a live birth was 1.3 pmol/L. CONCLUSIONS: Among women with a limited ovarian reserve, pre-treatment serum AMH levels significantly predicted failure to reach the classical hCG triggering criteria and predicted lack of follicular development using a new sensitive assay, but AMH was not suitable for withholding fertility treatment, as even very low levels were associated with live births. TRIAL REGISTRATION: Not relevant